Przedsiębiorca jako strona wyzyskana w rozumieniu art. 388 k.c. - Lewandowski, Paweł (PRAWO i WIĘŹ, 2026)
It has not yet been decided whether the exploitation regulated by Article 388 of the Civil Code applies to all types of transactions – particularly commercial transactions. The legislature has not clarified the subject-related prerequisites of exploitation, using only the general terms ”party,” i.e., exploiter and exploited. The purpose of this study is to provide a detailed analysis of the situation of an entrepreneur as an exploited party within the meaning of Article 388 of the Civil Code. First, it is demonstrated that an entrepreneur falls within the scope of application of Article 388 of the Civil Code. Next, the arguments supporting the possibility of recognizing an entrepreneur as an exploited party within the meaning of Article 388 of the Civil Code are presented and analyzed. Among these, the grounds for exploitation were discussed; attention was drawn to the most recent legislative amendment, together with the explanatory memorandum to the draft legislation; arguments based on the legal nature of exploitation, the protection of the parties’ contractual autonomy, and the wording of Article 1 of the Civil Code were then put forward.